Effect of packaging and storage on Aspergillus spp. and aflatoxin production in peanuts - John, Joshua Mark (2020)
Peanuts are most susceptible to mycotoxins contamination especially aflatoxins, which are class one carcinogenic mycotoxins vastly produced by Aspergillus flavus and Aspergillus parasiticus. They can induce both mutagenic and hepatogenic effect causing conditions such as immunosuppression and hepatic carcinoma. Due to the high temperature and humidity conditions in tropical and subtropical regions, high presence of aflatoxins can be expected. The purpose of the present study was to investigate, a) The effects of different packaging materials, temperatures and water activities on the aflatoxin B1 production by Aspergillus flavus and A. parasiticus in stored peanuts, b) To optimize the best storage conditions for the reduction of aflatoxin B1, total aflatoxins and growth of Aspergillus flavus and A. parasiticus in stored peanuts. On the first objective, peanut samples were randomly collected from supermarkets around Serdang, Selangor. The samples were separated into three different packaging materials (low density polyethylene [LDPE], polypropylene [PP] and polyethylene laminated aluminium [PELA]), inoculated and stored under temperatures of 25°C and 30°C, water activities (aw) of 0.80 and 0.95. For A. flavus stored in PELA, no AFB1 was detected (100% reduction) at 25°C for both aw tested. For A. parasiticus stored in PELA, no AFB1 was detected at 25°C (0.85 aw) and 30°C (0.74 aw). Lowest concentration of AFB1 was detected in PELA for both A. flavus and A. parasiticus, followed by PP and LDPE. For the second objective, peanut samples were separated into two packaging materials, PELA and PP, inoculated directly with A.flavus and A.parasiticus spores in concentration ranging from 101 to 106 spores per ml and stored under temperature of 30°C and relative humidity of 65 and 95% for 42 days (6 weeks). Results showed that significant (P < 0.05) response surface models with high coefficient of determinations (R2) with a range from 0.849 to 0.997 were able to be fitted to assess the AFB1 and AFT formation levels as functions of storage condition variables with more than 84% of variability of AFB1 and AFT formation could be explained by the significant (p < 0.05) nonlinear functions of time and initial spore inoculum levels. The main effects of time and initial spore inoculum level has significant (p < 0.05) effect on the formation of both AFB1 and AFT formation in the artificially inoculated air packed stored peanuts. For PP-FL 65, PP-AP-65, PELA-FL-65, PELA-AP-65, PP-FL-95, PP-AP-95, PELA-FL-95 and PELA-AP-95 the quadratic effects of both time and initial spore inoculum level showed significant (p < 0.05) effect on fungal growth. For the interaction effects, no significant (p > 0.05) effect was shown for all experimental runs and that both time and initial spore inoculum level had significant (p < 0.05) effect on values of all target AF’s and Aspergillus spp. growth. Optimum storage conditions for the best reduction of Aspergillus spp. growth and AF’s formation were able to be identified.